2013
DOI: 10.1021/nl4018385
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanostructure-Decorated TiO2 Nanowires Exhibiting Photoactivity Across Entire UV-visible Region for Photoelectrochemical Water Splitting

Abstract: Here we demonstrate that the photoactivity of Au-decorated TiO2 electrodes for photoelectrochemical water oxidation can be effectively enhanced in the entire UV-visible region from 300 to 800 nm by manipulating the shape of the decorated Au nanostructures. The samples were prepared by carefully depositing Au nanoparticles (NPs), Au nanorods (NRs), and a mixture of Au NPs and NRs on the surface of TiO2 nanowire arrays. As compared with bare TiO2, Au NP-decorated TiO2 nanowire electrodes exhibited significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
509
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 829 publications
(548 citation statements)
references
References 56 publications
12
509
4
1
Order By: Relevance
“…Hydrogen production by solar water splitting with semiconductor photocatalysts is a promising technology based on renewable resources [1,2]. Since the first report on water splitting by Fujishima and Honda, TiO 2 has been extensively investigated as an excellent photocatalyst due to its good stability, non-toxicity, low cost and high photocatalytic activity under UV light irradiation [3][4][5]. However, TiO 2 can only absorb UV light that makes up approximately 5% of sunlight, resulting in low light utilization efficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen production by solar water splitting with semiconductor photocatalysts is a promising technology based on renewable resources [1,2]. Since the first report on water splitting by Fujishima and Honda, TiO 2 has been extensively investigated as an excellent photocatalyst due to its good stability, non-toxicity, low cost and high photocatalytic activity under UV light irradiation [3][4][5]. However, TiO 2 can only absorb UV light that makes up approximately 5% of sunlight, resulting in low light utilization efficiency [6].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid photocatalytic systems developed by anchoring DMAP- 20 Au NPs on N-TiO 2 nanowires exhibit interesting optical and photocatalytic properties for water oxidation. Nitrogen doping of TiO 2 both maximizes the DMAP-Au NPs loading and improves the optical absorption due to band narrowing effect.…”
Section: Discussionmentioning
confidence: 99%
“…4b), the peaks at 396.8, 398.8, and 400.6 eV provide a clear picture of nitrogen environment at TiO 2 NWs. The peak at 396.8 eV is 20 attributed to the existence of atomic β-N at TiO 2 matrix and the peak at 398.8 eV implies the substitution of O 2 -by nitrogen ions and thus, results in the formation of N-Ti-O. 42,43 This confirms the existence of Ti 3+ due to the incorporation of nitrogen atoms into oxygen lattice sites.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…[112][113][114] The reports attributed the enhancements by the Au attachments mainly to hot electron transfers to semiconductors. Zhang et al demonstrated that Au nanocrystals attached to photonic crystal substrate composed of TiO 2 nanotubes yielded a photocurrent density of ca.…”
Section: -7mentioning
confidence: 99%